IMPROVING THE QUALITY OF TEMPEH MSMEs THROUGH SOCIALIZATION ON EFFECTIVE LABELING AND PACKAGING IN KEDUNGJAYA VILLAGE, KEDAWUNG DISTRICT, CIREBON - Gian Fitralisma; Hartanto Halim; Winda Dwi Yanthi; Arin Arin; Armada Trisakti; Ellin Herlina; Juni Hartono (Ann Publisher, 2025)
Abstrack Background: This program was conducted in the form of a socialization initiative involving KKN students from STIE Cirebon. The socialization focused on educating MSME (Micro, Small, and Medium Enterprises) actors about informative label design, packaging techniques that preserve product quality, and the benefits of attractive packaging in marketing. This community service activity aimed to enhance the understanding of tempeh MSME entrepreneurs in Kedungjaya Village regarding the importance of labeling and packaging in increasing product competitiveness. Method: This program used socialization, involving KKN students and tempeh MSME entrepreneurs in Kedungjaya Village. The socialization covered the importance of labeling and packaging, effective label design strategies, and proper packaging techniques that meet standards to maintain product quality and enhance its market appeal. Results: The findings indicate that KKN students played a crucial role in providing insights to MSME entrepreneurs on more effective labeling and packaging strategies. The observed positive impacts include an increased understanding among MSME entrepreneurs regarding the importance of packaging and the adoption of improved packaging techniques. Conclusion: Despite implementation challenges, collaboration between students, MSME entrepreneurs, and the local community was key to the program's success. Implications: Enhancing knowledge of labeling and packaging can help MSMEs improve product competitiveness, expand market access, and promote business sustainability. Therefore, continuous mentoring and strengthening of marketing infrastructure are strategic steps to ensure the long-term benefits of this program.